Kajian Free Trade Zone (FTZ) Batam-Bintan-Karimun (Permasalahan, Implementasi, dan Solusinya) - Muhammad Zaenuddin (EKO-REGIONAL, 2012)
Based on UU No 44 Tahun 2007 Free Trade Zone (FTZ) is applied in Batam, Bintan, and Karimun (BBK). Actually, FTZ has been implemented before that regulation was issued. It was indicated by giving incentive and eliminating of PPN and PPnBM. By means of issuing that regulation, the legality of FTZ implementation, hopefully it becomes a great momentum to attractive more investors. This research is aimed to identify the problems faced by operational institutions, Dewan Kawasan (DK) and Badan Pengusahaan Kawasan Batam, Bintan, and Karimun, deal with FTZ. It also aims to study deeply how many industrial business give response of that implementation. The research method applied is direct interview to the key persons in FTZ institution and businessmen of manufactures. This research finds the facts that FTZ of BBK has not been implemented well so it is needed improvement in regulation and organization structure of operational institution. Beside that, the implementation of FTZ, since April 1, 2009, has not completed by supporting tools such as organization and aparatures that ought to be ready for system and regulation changes from bonded zone to free trade zone. This research gives shorterm and longterm recommendations. For shorterm one it is needed to arrange development roadmap of FTZ and for longterm one it is important to set up grand strategy or blue print of FTZ development. Keywords: Free Trade Zone (FTZ), Dewan Kawasan, Badan Pengusahaan Kawasan